IMPLEMENTATION OF REAL TIME RELEASE TESTING ON DOXYCYCLINE CAPSULE MIXING PROCESS IN PT. PQR - Kesuma Suryaloka, Cahyani
Along with technology development in pharmaceutical industry, currently process of quality product measurement has been develop into real time measurement during the process or Real Time Release Testing (RTRT) using Process Analytical Technology (PAT) tools that is near infrared spectroscopy. This study aims to implement Real Time Release Testing (RTRT) to replace conventional quality product measurement with sampling along the process and followed by offline measurement. In this study, mixing process of Doxycycline Capsule was carried out and conducted in-line measurement of Critical Quality Attribute (CQA) i.e. blend homogeneity using near infrared spectroscopy. Then, proceed with capsule filling process and samples were taken to measure content uniformity of the product using HPLC (High Pressure Liquid Chromatography) method. Based on the research, the mixing of Doxycycline capsules with number of revolutions of 100 and speed of 11 rpm (revolutions per minute) was scanned and processed data spectrum using Moving Block Model (MBM) with F-test statistical analysis, the result was F value below the critical F value which was in the state of homogeneous condition. After filling process, the results of content uniformity using HPLC (High Pressure Liquid Chromatography) method showed that Relative Standard Deviation value for each sampling interval below 5.00%, the value of each individual sample fall between 90.00 - 120.00%, and the L1 value is less than 15.0. The results of capability analysis process provide value of centering capability index (Cpk) 1.63 and performance centering index (Ppk) 1.62, which indicates that the process of inter and intra batch are satisfactory, reliable, and consistent. Based on the research results, the real-time release testing process of the Doxycycline Capsule mixing process can be applied at PT. PQR.